Treatment of pancreatic head cancer with obstructive jaundice by endoscopy ultrasonography-guided gastrojejunostomy: A case report and literature review. Issue 28 (July 2018) - Shen, Zhaohua; Tian, Li; Wang, Xiaoyan
Abstract: Rationale: Ultrasonography-guided gastrojejunostomy (EUS-GJ) might be a safe, innovative and minimally invasive interventional treatment for patients with gastric outlet obstruction (GOO) as an alternative to the surgical approach. To date, few cases have been reported in the literature. Patient concerns: A case of pancreatic head carcinoma with obstructive jaundice occurred in a 78-year-old man with a prior history of pancreatic head cancer. Biliary stent placement was conducted 1 year earlier. Diagnoses: The patient was diagnosed with pancreatic cancer, pulmonary infection, pyloric obstruction, and biliary stent implantation. Interventions: EUS-GJ was performed. The wire and a double-balloon catheter reached the position of stenosis, then a double mushroom head bracket was released under EUS. The position was confirmed via X-ray. Outcomes: The symptoms of obstruction were alleviated. No recurrence of obstruction, bleeding, perforation, and other complications occurred for the following 1.5 months while he died because of whole body spread of pancreatic cancer. Lessons: EUS-GJ may be reliable and effective for patients with GOO.